Coleta seletiva em municípios do Pará : tomada de decisão com o Método AHP (Analytic Hierarchy Process) - Samara Avelino de Souza França (2024)
In Brazil, the Solid Waste (SW) National Policy recommends integrated and sustainable management. Among the management alternatives is the Selective Collection (SC), the national scenario of which is still incipient, as 68% of Brazilian municipalities didn't have it in 2021, with the percentage of 89% for the North region (Brasil, 2022c). Therefore, the general objective of the research was to analyze the management of SC in municipalities in the State of Pará, using the decision support method AHP - Analytic Hierarchy Process and, more specifically, i) analyze how SC has been carried out in the context of the some municipalities of Pará; ii) analyze the decision criteria with the greatest degree of importance for SC according to experts consulted; and iii) analyze the applicability of the AHP method for the management of SC in municipalities in Pará. As a methodology, the AHP method was used, using 16 SC Sustainability Indicators (Besen et al., 2017), considering municipalities in two Integration Regions of Pará (Guajará, and Guamá), as well as polo municipalities, as they concentrate more than 50% of waster pickers and recyclables sales points in the State. The selection of specialists considered three groups: group 1 – employees of Municipal Bodies responsible for SW management; 2 – representatives of associations or cooperatives of waste pickers; and group 3 – professors/researchers from universities of Pará. The expansion of SC in municipalities analyzed has been slow and carried out largely by autonomous pickers, although some organizations receive support from local governments. Furthermore, municipalities have sought to integrate it with environmental education actions in schools and socio-productive inclusion strategies for collectors. Of the groups that responded to the survey (1 and 3), the decision criteria with the greatest degree of importance were "Institutional" and "Costs" for Group 1; and "Relations with society" and "Efficiency" for Group 3, with the AHP recognized like an important tool to help for decision-making in the planning, operationalization and sustainability of SC in municipalities.